El liderazgo y su impacto en la productividad en la coac. de ahorro y crédito p.a.i.s. ltda. - Pinda Pomaquero, Byron Rolando (2025)
The current paradigm immerses us in an era where reflection gives way to pragmatism where electronic devices replace the human interactions. The unstoppable pursuit of success becomes a must to improve our quality of life and therefore, it is essential to set goals in the personal and professional fields. The achievement of these goals requires effective planning and execution where the technical, human, and strategic skills of the leaders emerge as fundamental elements. These skills serve as the link to connect the theory with its practical application facilitating the achievement of the collective and individual objectives. Leadership plays a crucial role in the business development, specially in the private and public sectors. The importance of leadership is highlighted in companies such as Riobamba Ltda. Cooperative in Chimborazo, where the influence of the leader is emphasized to achieve objectives aligned with values, beliefs, and principles. In the current context, leadership has become consolidated as a fundamental aspect of the organizational behavior, especially in financial institutions that seek growth and sustainable development. It is identified that the manager’s behavior influences the quality and success of the company in the market. In Riobamba, it is evident that the leadership from the family level to the community coordination in rural areas where productive activities are organized such as agriculture and livestock farming which are fundamental for the local economy and the daily sustenance of the population. The effective leadership is crucial for the success and sustainability for both the cooperatives and other organizations, especially in a context of globalization and economic development.